Sistema integrado de Proyectos Pecuarios en el Centro Experimental Académico Salache - López Toledo, Kevin Emiliano (2019)
The research project was carried out in the Salache Academic Experimentation Center (CEASA), part of the Technical University of Cotopaxi, which includes 13 projects with an academic focus. The objective of the research is to characterize the integrated system of livestock projects of the Academic Center Salache to determine the characteristics of the projects, the educational objective, and the productive and reproductive parameters; and by this way an integrated system where all CEASA livestock projects are merged. The characterization of the projects was carried out by generating descriptive indexes of the aspects or variables that are related to the components of the production system such as equipment, organizational aspects, animal health management, management, and food resources. The measurement instrument for the quantitative and qualitative characterization of the projects was based on a survey of 59 questions made to CEASA administrative staff. On-site visits, recognition and direct observation of the projects were carried out too. After the investigation, the spaces for which there is not enough data for the animal load are determined; the records that provide the information of the productive, reproductive and health parameters with the infrastructure are not available. All livestock projects have an academic focus that allows the articulation of teaching with practice, research, and linking, creating a public company where the economic management of the projects is allowed. The establishment of an integrated system of livestock projects could be articulated under an academic and research approach where all projects are combined and contribute to a macro project. They were also articulated through a system of self-sustainability integrating the productive parameters of the CEASA livestock projects.